2017
DOI: 10.3171/2017.7.focus17342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body mass index on surgical outcomes after posterior spinal fusion for adolescent idiopathic scoliosis

Abstract: OBJECTIVEObesity is an increasing public health concern in the pediatric population. The purpose of this investigation was to examine the impact of body mass index (BMI) on 30-day outcomes after posterior spinal fusion for adolescent idiopathic scoliosis (AIS).METHODSThe American College of Surgeons National Surgical Quality Improvement Program Pediatric database (2013 and 2014) was reviewed. Patients 10–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Prior studies have suggested that obese patients are at higher risk due to their larger surface area, which may increase the potential dead space and require greater force during intraoperative retraction, which may lead to tissue necrosis. [40][41][42][43] Prevention strategies for reducing the risk of postoperative wound infection include bacterial screening, the administration of preincision antibiotics, and meticulous sterile technique. The CMS has implemented various initiatives aimed at reducing the incidence of preventable surgical complications, including surgical site infection, by suggesting that it will no longer pay the additional cost associated with adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have suggested that obese patients are at higher risk due to their larger surface area, which may increase the potential dead space and require greater force during intraoperative retraction, which may lead to tissue necrosis. [40][41][42][43] Prevention strategies for reducing the risk of postoperative wound infection include bacterial screening, the administration of preincision antibiotics, and meticulous sterile technique. The CMS has implemented various initiatives aimed at reducing the incidence of preventable surgical complications, including surgical site infection, by suggesting that it will no longer pay the additional cost associated with adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Within the general spine literature, obesity has been widely associated with increased complication incidence. [34][35][36][37][38][39][40] Regarding surgical complications specifically, multiple studies have demonstrated an association between obesity and the incidence of surgical site infections. 35,38,39,41,42 The increased risk for surgical site infections in obese patients has been attributed to the increased risk of fat necrosis in this population, serving as a nidus for infection.…”
Section: Discussionmentioning
confidence: 99%
“…NSQIP-P has been used to describe adverse events following common pediatric orthopedic procedures in order to identify procedures and patient characteristics associated with an increased risk of postoperative complications [26]. Other studies have considered outcomes after specific orthopedic procedures [27][28][29], most frequently involving the spine [30][31][32][33], as well as outcomes in orthopedic patients with specific risk factors such as obesity, congenital heart disease, or cerebral palsy [34][35][36]. To our knowledge, NSQIP-P has not been used to characterize outcomes after pediatric orthopedic oncology procedures.…”
Section: Introductionmentioning
confidence: 99%